2022
DOI: 10.31579/2692-9392/160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Socio Demographic Data and Female Genital Mutilation

Hanan Elzeblawy Hassan

Abstract: Background: The World Health Organization and the United Nations Children's Fund and the United Nations Population Fund released the first joint statement directly addressing Fmale Genital Mutilation. Aim: Assess Relationship between Socio Demographic Data and Female Genital Mutilation at Beni-Suef. Subject & Methods: A descriptive cross-sectional study was used. The study population consisted of 2837 females in family health centers (FHCs) in different sitting at Beni-Suef. Α Structured Interviewing Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Regarding the association between attitudes and FGM, the result of the current study revealed that unfavorable attitude score was more prevalent among mutilated females, while the favorable attitude was associated with the absence of FGM. There was a significant relationship between FGM and the participant's attitude (p-value <0.001) [45][46]. This may attributed to their exposure to complications after FGM which affect them and left bad personal experiences.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the association between attitudes and FGM, the result of the current study revealed that unfavorable attitude score was more prevalent among mutilated females, while the favorable attitude was associated with the absence of FGM. There was a significant relationship between FGM and the participant's attitude (p-value <0.001) [45][46]. This may attributed to their exposure to complications after FGM which affect them and left bad personal experiences.…”
Section: Discussionmentioning
confidence: 94%
“…The first is that it would have been developed in Egypt and spread to other countries, while the second is that it originated in Africa as an African tribal puberty rite and then transmitted to other places like Egypt [5][6][7]. The origin of infibulation (type of FGM/C) is slightly difficult to be traced, but it'd be dated to the Romans, and mainly performed on slaves to stop them from making sexual relationships [8][9][10]. Within the 19th century, the UK allowed the removal of the females' clitoris surgically as a treatment for epilepsy, sterilization, and masturbation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%